2020
DOI: 10.1111/1750-3841.15436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions as high‐intensity ultrasound, agitation, and cooling temperature on the physical properties of a low saturated fat

Abstract: The objective of this work was to evaluate the effect that agitation rate, crystallization temperature, and sonication have on the physical properties of a soybean-based fat with low levels of saturated fatty acids crystallized in a scraped surface heat exchanger (SSHE). The sample was crystallized at two temperatures (20 and 25°C) and agitation rates (344/208 rpm in the barrels/pin worker-high agitation HA and 185/71 rpm barrels/pin worker-low agitation LA), and a constant flow of 11 L/hr. High-intensity ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The presence of these many small crystals could have increased the hardness for samples with the same SFC due to the small crystals forming a tighter, more uniform crystal matrix compared to large crystals. Similar results were found by other authors (da Silva, Cooper, et al, 2020;da Silva, Danthine, & Martini, 2020;Kerr et al, 2011;Suzuki et al, 2010;Wagh et al, 2013;Ye et al, 2011;Ye & Martini, 2015), where the application of HIU resulted in smaller crystals, no differences in SFC, and harder materials.…”
Section: Hardnesssupporting
confidence: 91%
See 2 more Smart Citations
“…The presence of these many small crystals could have increased the hardness for samples with the same SFC due to the small crystals forming a tighter, more uniform crystal matrix compared to large crystals. Similar results were found by other authors (da Silva, Cooper, et al, 2020;da Silva, Danthine, & Martini, 2020;Kerr et al, 2011;Suzuki et al, 2010;Wagh et al, 2013;Ye et al, 2011;Ye & Martini, 2015), where the application of HIU resulted in smaller crystals, no differences in SFC, and harder materials.…”
Section: Hardnesssupporting
confidence: 91%
“…Oil loss OL was measured using a centrifuge method previously described in other studies (da Pieve et al, 2010;da Silva, Cooper, et al, 2020;da Silva, Danthine, & Martini, 2020;da Silva, Marsh, et al, 2020;Giacomozzi et al, 2019). Approximately 1 g of the sample was placed in a pre-weighed microcentrifuge tube, placed in a centrifuge, and spun for 15 min at 10,000 rpm.…”
Section: Melting Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The abbreviation HIU‐0 is used when HIU is placed before the first barrel, HIU‐1 corresponds to having HIU between the two barrels, in HIU‐2 the HIU is placed after the second barrel (and before the PW), and HIU‐3 indicates that the HIU is placed after the PW when crystallization in the SSHE is completed (da Silva & Martini, 2019). These studies found that the induced sonocrystallization was affected by the chemical composition of the lipid used (da Silva et al, 2021a; da Silva, Danthine, et al, 2020) and by sonocrystallization conditions (da Silva & Martini, 2019) as observed in a batch condition. Nevertheless, SSHE crystallization conditions also played an important role, such as (1) Step of crystallization where HIU is applied (HIU‐0, HIU‐1, HIU‐2, and HIU‐3).…”
Section: Sshe Combined With New Technologiesmentioning
confidence: 99%
“…Recent innovations in the use of SSHE have also been reported, mostly combining SSHE crystallization with other equipment such as high-intensity ultrasound (HIU), high-pressure homogenizer, or other crystallization units. For HIU, authors have induced crystallization and improved physical properties of different fats by coupling the HIU in different stages of the SSHE (da Silva et al, 2021a(da Silva et al, , 2021bda Silva, Danthine, et al, 2020;da Silva & Martini, 2019;da Silva & Martini, 2020a, 2020b. SSHE has also been coupled in a double-stage homogenizer (DSH) to produce zero-trans margarine with minimized post-hardening crystallization (Miskandar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%